Macromineral requirements for maintenance and growth of Saanen goats - Castillo Vargas, Julián Andrés [UNESP] (2017)
The objective of this study was to evaluate the effect of sex on the net macromineral requirements for maintenance and growth of Saanen goats from 5 to 45 kg body weight (BW). For this purpose, three dataset were used: the first dataset was assembled to evaluate the effect of sex on the net requirements for maintenance of Ca (NCam), P (NPm), Mg (NMgm), and K (NKm), estimated using the comparative slaughter technique (CST). This dataset was composed by 154 individual records (53 castrated males, 46 females, and 55 intact males) from three comparative slaughter studies. The second dataset, was constructed to evaluate the effect of sex on NCam, NMgm, and NKm, estimated using the minimum endogenous losses method (MEL). This dataset was assembled with 155 individual records (67 castrated males, 40 females, and 48 intact males) from four feeding trials. The third dataset was constructed to evaluate the effect of sex on the net requirements for growth of Ca (NCag), P (NPg), Mg (NMgg), Na (NNag), and K (NKg) considering or not the degree of maturity of the goat on the estimations. This dataset comprised by 209 individual records (69 castrated males, 69 females, and 71 intact males) from six comparative slaughter studies. Mineral requirements for maintenance using CST were calculated from the intercept of the linear regression between mineral retention and the mineral intake. Using the MEL, mineral requirements for maintenance were calculated from the intercept of a linear regression between mineral excreted (urine and feces) and mineral intake. The estimation of NPm using MEL was not possible, because of the lack of enough information on P excretion and intake from feeding trials, to fit equations for calculating its requirements. The NCag, NPg, NMgg, NNag, and NKg were estimated by the first derivative of the logarithmized allometric equations. The studies were performed as meta-analyses, considering sex as fixed effect and study as random effect. Sex did not affect NCam, NPm, and NKm estimated using CST (P > 0.10). Estimated NCam, NPm, and NKm using CST were 21.1, 22.8, and 3.99 mg/(kg BW·d), respectively, from 5 to 45 kg BW. On the other hand, NMgm of intact males (2.65 mg/(kg BW·d)) were greater than that estimated for castrated males and females (1.39 mg/(kg BW·d); P < 0.10). Similarly, sex did not affect NCam, NMgm, and NKm estimated by MEL (P > 0.10). The NCam, NMgm, and NKm values were 38.0, 7.45, and 25.2 mg/(kg BW·d) respectively, from 5 to 45 kg BW. With respect to mineral requirement for growth, without considering the degree of maturity, sex did not affect the NCag, NPg, NNag, and NKg (P > 0.10). The NCag and NPg remained constant, whereas NNag and NKg decreased by 32 and 27%, respectively, from 5 to 45 kg BW. On the other hand, sex affected the NMgg (P = 0.054), where the NMgg of castrated and intact males were 8 and 18%, respectively greater than those female goats. The NMgg of castrated and intact males increased 8 and 15%, respectively, whereas NMgg of females decreased by 8% from 5 to 45 kg BW. Considering the degree of maturity, sex affected all net macromineral requirements for growth (P < 0.10). The NCag and NPg of intact males were 5 and 2% respectively greater than those of castrated males and females. Besides, the NCag and NPg remained constant from 5 to 45 kg BW across sexes. The NNag of males were 6% greater than those females. Irrespective of sex, NNag decreased by 32% from 5 to 45 kg BW. Regardless of sex, NKg decreased by 26% from 5 to 45 kg BW. The NMgg of castrated and intact males were 7 and 17%, respectively greater than those of female goats. The NMgg of castrated and intact males increased 8 and 16%, respectively, whereas NMgg of females decreased by 7% from 5 to 45 kg BW. Our studies indicate that sex influences mineral requirements for maintenance and growth as well as the mineral retention efficiency of Saanen goats. This information may be useful to design strategies for optimizing the mineral recommendations to goats.